Live streamed music as a post-COVID-19 urban trend: accessing TME live in China’s mediascape as an alternative concert experience - Li, Fan; Chow, Ow Wei (Human Resource Management Academic Research Society (HRMARS), 2023)
Since its rapid outbreak, COVID-19 had caused a huge financial loss for all walks of life in global (Szmigiera, 2021). Seeking alternatives out of the immediately enforced social-distancing policy, music performers worldwide have turned to digitally stream-based platforms, which have perhaps discarded consumers’ usual habit of accessing live music. This phenomenological study aims to explore the impact of accessing popular music in the early COVID-19 pandemic period with a focus on online events by TME Live, which appears as an innovator in China’s streamed media industry. The lived experience of the phenomenologists in designated events is accounted in order to investigate China’s popular music scene in the pandemic time with a special interest to problematize emerging urban trends in experiencing popular music via Chinese media post-COVID-19. This study is to offer a substantial reference in researches on COVID-19-influenced urban lifestyle through experiencing popular music in a ‘new normal’ cosmopolitan mediascape.